Unveiling the nanoworld of antimicrobial resistance: integrating nature and nanotechnology - Sharma, Devesh; Gautam, Sakshi; Singh, Sakshi; Srivastava, Nalini; Khan, Abdul Mabood; Bisht, Deepa (Frontiers in Microbiology, 2025)
A significant global health crisis is predicted to emerge due to antimicrobial resistance by 2050, with an estimated 10 million deaths annually. Increasing antibiotic resistance necessitates continuous therapeutic innovation as conventional antibiotic treatments become increasingly ineffective. The naturally occurring antibacterial, antifungal, and antiviral compounds offer a viable alternative to synthetic antibiotics. This review presents bacterial resistance mechanisms, nanocarriers for drug delivery, and plant-based compounds for nanoformulations, particularly nanoantibiotics (nAbts). Green synthesis of nanoparticles has emerged as a revolutionary approach, as it enhances the effectiveness, specificity, and transport of encapsulated antimicrobials. In addition to minimizing systemic side effects, these nanocarriers can maximize therapeutic impact by delivering the antimicrobials directly to the infection site. Furthermore, combining two or more antibiotics within these nanoparticles often exhibits synergistic effects, enhancing the effectiveness against drug-resistant bacteria. Antimicrobial agents are routinely obtained from secondary metabolites of plants, including essential oils, phenols, polyphenols, alkaloids, and others. Integrating plant-based antibacterial agents and conventional antibiotics, assisted by suitable nanocarriers for codelivery, is a potential solution for addressing bacterial resistance. In addition to increasing their effectiveness and boosting the immune system, this synergistic approach provides a safer and more effective method of tackling future bacterial infections.